The Impact of Entrepreneurial Knowledge on College Students' Entrepreneurial Interest with Self-Efficacy as a Mediating Variable - Hary Yanto Jailani; Nofialdi Nofialdi; Zulvera Zulvera (ITScience (Information Technology and Science), 2026)
This research endeavors to examine the effect of entrepreneurial knowledge on students' entrepreneurial interest, with self-efficacy serving as a mediating variable. The primary focus of the research is on students who have completed the Independent Business Project (Proyek Usaha Mandiri, PUM) course in the agricultural sector at Politeknik Pertanian Negeri Payakumbuh. The methodology employed is a descriptive research design utilizing a survey method, wherein primary data were collected through structured questionnaires. The research sample consisted of 35 respondents selected using a multiple stage sampling technique. Data analysis was conducted using the Partial Least Square (PLS) structural equation modeling approach. The findings reveal that entrepreneurial knowledge exerts a significant influence on self-efficacy (p-value = 0.000), indicating that mastery of operational, marketing, and financial content provides a cognitive foundation for students to assess their own capabilities in managing business ventures. Furthermore, self-efficacy was found to have a significant effect on entrepreneurial interest (p-value = 0.000), demonstrating that belief in one's personal capacity serves as the primary psychological driver in choosing an entrepreneurial career path. The mediation test confirms that self-efficacy plays a significant role as a